2010
DOI: 10.1016/j.carj.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality in Low-dose Multidetector Computed Tomography: A Pilot Study to Assess Feasibility and Dose Optimization in Whole-body Bone Imaging

Abstract: Whole-body low-dose CT can be used to obtain adequate CT image quality to assess normal osseous detail while delivering effective doses similar to those associated with conventional radiographic skeletal survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…The widespread availability of multi-detector CT scanners has contributed to the increased use of WBLDCT for the diagnosis and follow-up of MM. The total effective dose of the WBLDCT in our study is comparable to those reported in recent literature [24][25][26][27]. Moreover, our measured organ specific dose is comparable to the organ dose described by Kröpil DLP dose length product, CTDI vol volume computed tomography dose index, NA not applicable/available et al [28].…”
Section: Discussionsupporting
confidence: 88%
“…The widespread availability of multi-detector CT scanners has contributed to the increased use of WBLDCT for the diagnosis and follow-up of MM. The total effective dose of the WBLDCT in our study is comparable to those reported in recent literature [24][25][26][27]. Moreover, our measured organ specific dose is comparable to the organ dose described by Kröpil DLP dose length product, CTDI vol volume computed tomography dose index, NA not applicable/available et al [28].…”
Section: Discussionsupporting
confidence: 88%
“…Both for female and male patients an effective dose of approximately 4.8 mSv was calculated using these parameters 12 . The most exhaustive comparison of the effect of dose parameters on bone image quality at WBLDCT was performed by Gleeson et al, who applied 14 different WBLDCT protocols on a single cadaver, using various combinations of tube voltage (ranging from 80 to 140 kV) and time-current product (ranging from 14 to 125 mAs) 20 . Image quality of each data set was rated on a five-point scale ranging from “very good” to “poor and/or nondiagnostic”.…”
Section: Acquisition Of Imagesmentioning
confidence: 99%
“…In our experience, the doses received by patients were not higher than the ones received during standard upper series. In addition, the radiation exposure can be still reduced while preserving image quality using both low-dose CT protocols [17] and up-to-date work station, as currently assessed in our centre.…”
Section: Discussionmentioning
confidence: 95%